Dukungan Suami Berhubungan dengan Kecemasan Ibu Bersalin Primigravida - Siti Asiyah; Syarifatul Aini (STIKES Karya Husada Kediri, 2021)
Abstract Primigravida maternal anxiety can affect the state of the mother and baby in the delivery process. Positive husband support for the wife will have a positive impact on the physical and psychological health of the mother in the process of childbirth. The research objective was to determine the relationship between husband's support and anxiety of primigravida maternal mothers. The study was conducted on 22 August-25 September 2020. Quantitative analytic survey research design with cross sectional approach. The independent variable is husband's support and the dependent variable is primigravida maternity anxiety. The study population was all primigravida maternal in the Maternity Room of Prima Medika Hospital Tulungagung totaling 142 people. The research sample was taken by consecutive sampling technique with a total of 35 respondents. The research instrument used a questionnaire about husband's support and the level of maternal anxiety. Data were analyzed using the Spearman Rho test. The results showed that most respondents received positive support from their husbands in facing childbirth as many as 19 respondents (54.3%). Nearly half of the respondents did not experience anxiety as much as 17 respondents (45.6%) and experienced mild anxiety as many as 13 respondents (37.1%). The results of the Spearman Rho statistical test obtained p value = 0.000 < 0.05 so that there is a relationship between husband's support and the anxiety of primigravida maternity with a correlation coefficient value of 0.691 meaning that the level of closeness of the relationship is in the strong category. Primigravida mothers who get support from their husbands well in dealing with childbirth will not experience anxiety when facing childbirth. This is because mothers who get support from their husbands feel comfortable, more confident and strong in facing childbirth. Keywords: Husband's Support, Anxiety, Primigravida Maternity.